Peran Orang Tua Dalam Pendidikan Akhlak Anak Sejak Dini Dalam Sudut Pandang Al-Qur'an - Wardah Yuni Kartika; Lidya Zanti; Dini Gita Sartika; Zaky Raihan; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
It has become an axiom that parents are responsible for their children's education. Parents are the first teachers for children. It is appropriate that since waiting for the birth of a child, even before marriage, prospective parents have planned how to raise and educate their children. The aim of this research is to describe the responsibilities of parents in raising children at an early age based on al-Maragh's interpretation of the Al-Qur'an verse 9 of Surah An-Nisa. This research uses a qualitative research method with a library approach, the main source of information is obtained from reading materials from books, magazines, articles and interpretations of the al-Maragh hadith which contain the thoughts of Imam al-Maragh. Data analysis was carried out through the following stages: data processing (unification), data classification, data interpretation. This research produced several results. First, the Al-Qur'an, Surah Al-Nisa verse 9, contains a warning to every parent that they will be worried and afraid if in the future they have to leave their child in a weak and helpless state. Second, parents are responsible for educating young children. The areas of education that are the responsibility of parents are physical and spiritual education, religious education, and character education.